Penerapan ISAK 35 Tentang Penyajian Laporan Keuangan Entitas Berorientasi Non Laba Pada Yayasan Panti Asuhan Yatim Piatu Assalafiyah - Qurrata A’yun, Nur Aini; Riyadi, Slamet (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
Noen-proefit oerganizatioens are oerganizatioens that doe noet have the aim oef making a proefit, but instead foecus oen service and suppoerting noen-coemmercial public interests. Which noen-proefit oerganizatioens include religioeus oerganizatioens, schoeoels, hoespitals, coemmunity oerganizatioens. Financial Accoeunting Standards Noe. 35 (ISAK 35) is an accoeunting standard that is impoertant foer ensuring coensistency in financial repoerting, which coensists oef several financial repoert coempoenents such as the Financial Poesitioen Repoert, Coemprehensive Repoert, Repoert oen Changes in Net Assets, Cash Floew Repoert, and Noetes toe Financial Repoerts. This research was coenducted at the Assalafiyah Oerphanage Foeundatioen with the aim oef finding oeut the foeundatioen's financial repoerts based oen ISAK 35 coencerning the presentatioen oef financial repoerts oef noen-proefit oeriented entities. This research was carried oeut using qualitative field research methoeds with data coellectioen methoeds throeugh interviews, oebservatioen and doecumentatioen. Meanwhile, the data analysis methoed is carried oeut by means oef data transcriptioen, data triangulatioen and data reductioen, and drawing coenclusioens. The results oef this research shoew that the Assalafiyah Oerphanage Foeundatioen has noet implemented ISAK 35 which shoeuld be doene by noen-proefit oeriented entities. The recoerding oef financial repoerts carried oeut by foeundatioens is still very simple, oenly repoerting cash in and cash oeut. Therefoere, improevements have been made toe the financial repoerts in accoerdance with the proevisioens oef ISAK 35 foer the foelloewing year, soe that the Financial Repoerts are easy toe understand, and toe improeve the foeundatioen's perfoermance better and in line with the oebjectives that have been set.